Women's healthcare decision-making and unmet need for contraception in Mali - Edward Kwabena Ameyaw; Abdul-Aziz Seidu; Bright Opoku Ahinkorah (BMC, 2022)
Plain Language summary Evidence suggests that reproductive health rights influence contraception use. In Mali, women are noted to have limited control over their healthcare decisions. Due to that, this current study explored the relationship between women's healthcare decision-making capacity and unmet need for contraception in Mali. The sample was 6593 women aged 15-49. About nine out of ten of the women were not taking their healthcare decisions alone and 35.7% indicated that they had unmet need for contraception. Unmet need for contraception dominated among those aged 45-49 (50.9%) but was low among those aged 15-19 (19.2%). Women who took their healthcare decisions alone had high odds of unmet need for contraception. Compared with women aged 15-19, unmet need was nearly five times likely among women aged 45-49. Richer women had lower odds of unmet need for contraception compared with poorest women. To increase contraceptive use in Mali, it is important to take into consideration the variations revealed in this study. This will help to strengthen existing policies geared towards fertility control and improvement in maternal health.